The Role of Inner Speech in Executive Functioning Tasks: Schizophrenia With Auditory Verbal Hallucinations and Autistic Spectrum Conditions as Case Studies - Petrolini, Valentina; Jorba, Marta; Vicente, Agustín (Frontiers in Psychology, 2020)
Several theories propose that one of the core functions of inner speech (IS) is to support subjects in the completion of cognitively effortful tasks, especially those involving executive functions (EF). In this paper we focus on two populations who notoriously encounter difficulties in performing EF tasks, namely, people diagnosed with schizophrenia who experience auditory verbal hallucinations (Sz-AVH) and people with Autism Spectrum Conditions (ASC). We focus on these two populations because they represent two different ways in which IS can fail to help in EF tasks, which can be illustrative for other mental conditions. First, we review the main components of EF (Section 1). Then we explain the functions that IS is taken to perform in the domain of EF (Section 2) and review the evidence concerning problems about EF in the two populations of our study: Sz-AVH (Section 3) and ASC (Section 4). After this we further detail our account about what a properly functioning IS can do for both populations and how different IS profiles may impact EF performance: in the case of Sz-AVH, the uncontrolled and intrusive character of IS negatively affects EF performance, whereas in ASC, EF is not sufficiently supported by IS, given the tendency in this population to present a diminished use of IS (Section 5). We finally briefly discuss Attention Deficit/Hyperactivity Disorder (ADHD) and Developmental Language Disorders (DLD) (Section 6).